Unveiling non-equilibrium metallurgical phases in dissimilar Al-Cu joints processed by vaporizing foil actuator welding. (15th January 2020) - Wang, Kaifeng; Shang, Shun-Li; Wang, Yuxiang; Vivek, Anupam; Daehn, Glenn; Liu, Zi-Kui; Li, Jingjing
Abstract: An integrated experimental and computational approach has been adopted to investigate the formation mechanism of intermetallic compounds (IMCs) in dissimilar Al-Cu joints processed by vaporizing foil actuator welding (VFAW). Aiming to understand the formation of IMCs and their transition, the present work employed first-principles calculations of thermodynamic properties as a function of temperature and pressure together with diffusivities of Al and Cu from the literature. Agreeing with experimental observations, the predicted IMC formation sequence in the low-energy welding region is as follows. θ-Al2 Cu forms first due to the fast diffusivity of Cu in the Al-matrix. θ-Al2 Cu then transforms to η2 -AlCu because of the fast diffusivities of Al/Cu in θ-Al2 Cu. In the high-energy welding region, the stable γ 1 -Al4 Cu9 and the metastable θ''-Al3 Cu are also formed in addition to the aforementioned θ-Al2 Cu and η2 -AlCu. η2 -AlCu and considerable γ 1 -Al4 Cu9 are the major phases in the high-energy welding region. The present approach, combining experiments and calculations, is proven to be a practical way to understand non-equilibrium metallurgical processes, as demonstrated through the study of VFAW Al-Cu joints. Graphical abstract: Image 1 Highlights: Stable and metastable Al-Cu intermetallic compounds are characterized experimentally. Formation of Al-Cu intermetallic compounds is mainly controlled by diffusion and temperature. An integrated approach is proposed to understand non-equilibrium metallurgical processes.